The Effect Of Video Recording As Media Towards The Students’ Speaking Skill In Online Class - vivi oktaviani (Universitas Pahlawan Tuanku Tambusai, 2021)
This research aims to find out whether there is an effect on using Video recording as media towards the students’ speaking skill in online class, in academic year 2019/2020. This research is a quasi-experimental research. It involved 48 students of two class, class 8A as the control class and class 8D as the experimental class. Each class consisted of 24 students. The experimental class was taught by using Video recording as media and control class was taught without using Video Recording. The data were analyzed by using T-test formula. Based on the collecting data, it was obtained that is 7,03 and is 1,68 where is 0,05. It showed that higher than (7,03 higher than 1,68), so that is rejected and is accepted. It means there is a significant difference in the students’ speaking skill between the students who were taught by using Video Recording and those who were taught using teacher method. Based on the result findings, it can be concluded that the use of Video Recording in teaching speaking skill in online class is effective.